GAMBARAN PENDEKATAN BELAJAR DAN PERSEPSI TENTANG PROBLEM BASED LEARNING (PBL) MAHASISWA PSIK UR - Rukmana Rukmana; Herlina Herlina; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Problem Based Learning (PBL) is a learning approach that stimulates learners to study in groups in searching forsolutions from real-world problems.This study aims to know the discription of learning approach and perception aboutProblem Based Learning (PBL) of PSIK UR students with a descriptive research design using the simple randomsampling technique. This research involved 88 students of PSIK UR. The measuring tool used were the Study ProcessQuestionnaire (SPQ) and Problem Based Learning (PBL) perceptions that have been tested for the validity andreliability. The data analysis used was univariate data analysis with the result; there were 40 students (45,9%) usingdeep approach , 25 students (28,4%) using achieving approach, 22 students (25%) using surface approach, and relatedto the perception of Problem Based Learning (PBL ) it was found that 54 students (61,4%) had negative perception, and34 students (38,6%) had positive perception. Based on this research, the students are expected to be able to makechanges in deep learning approach, and finally they are able to increase their learning motivation so that they are ableto improve their learning achievement and critical thinking in solving problems through good ways.Keywords: Learning Approach, Perception, Problem Based Learning (PBL), Student